TRPC5OS induces tumorigenesis by increasing ENO1-mediated glucose uptake in breast cancer - Yangyang Cui; Jinghui Peng; Mingjie Zheng; Han Ge; Xiaowei Wu; Yiqin Xia; Yue Huang; Shui Wang; Yongmei Yin; Ziyi Fu; Hui Xie (Translational Oncology, 2022)
Breast cancer is the most common malignant tumor worldwide and the leading cause of cancer-related deaths in female. Metabolic reprogramming plays critical roles in breast tumorigenesis and induces enhanced glucose uptake and glycolysis. TRPC5OS is encoded by short transient receptor potential channel 5 opposite strand, and predicted to correlate with tumor metabolic reprogramming. Here we aim to elucidate the function of TRPC5OS in aberrant metabolism mediated tumorigenesis. We detected TRPC5OS expression levels in cell lines and tissues by quantitative real-time polymerase chain reaction and immunohistochemistry. Then we assessed the effects of TRPC5OS on proliferation and cell cycle progression in breast cancer cells by cell counting kit-8, colony-formation, EdU-incorporation assays and flow cytometry. Tumor growth in vivo was observed in a mouse xenograft model. Mass spectrum analyses were performed to identify potential interactors of TRPC5OS in tumor cells, and the interaction between TRPC5OS and interactors was validated by co-immunoprecipitation (CO-IP), western blots, and immunofluorescent staining. Glucose uptake was measured by liquid scintillation spectrometry. TRPC5OS highly expresses both in breast tumors and cell lines, and might be an independent prognostic marker for breast cancer patients. Overexpressed TRPC5OS promotes breast cancer cell proliferation, cell cycle progression, and enhances tumor xenograft growth. Mass spectral and CO-IP data showed that TRPC5OS interacts with ENO1. We also demonstrate that TRPC5OS could enhance ENO1/PI3K/Akt-mediated glucose uptake in breast cancer cells. Our study demonstrated that TRPC5OS promotes breast tumorigenesis by ENO1/PI3K/Akt-mediated glucose uptake. TRPC5OS might be an independent prognostic marker and potential therapeutic target for breast cancer patients.